Phenomena Of English Teacher Education Graduates Choosing Careers Other Than Teaching - Rizqi, Satria Dyan; Retnaningdyah, Pratiwi; Lestari, Lies Amin (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The phenomena of education graduate alumni selecting non-teaching employment was the main focus of this qualitative study on the employability of teacher education graduates after graduation. The present non-teaching jobs, the reasons behind the non-teaching career choice, the skills and abilities useful to their current work, and their opinions and feelings regarding their non-teaching occupation were all described using an interpretive phenomenology. One-on-one online interviews were used to collect the qualitative data, 3 categories were created in order to address specific research concerns. According to this research, there are three categories of non-teaching occupations currently held by graduates of teacher education programs: office work, non-education related training positions, and service and management. After careful investigation, it was also shown that graduates chose non-teaching careers due to their lack of commitment to the teaching profession, contextual influence, competitive pay, support for their passion and growth, flexibility, and desire for a balanced life. Additionally, professional values and attitudes, transversal skills, learning skills, documentation, and teaching abilities were useful qualities for their current non-teaching position. Graduates in teacher education who are not in teaching feel happy, fulfilled, and flexible. The results indicate that the basic competencies obtained in the Teacher Education Program (TEP) provide a multitude of skills that significantly enhance one's capacity to be flexible, adaptive, and productive in non-teaching roles.